97 COVID Check-In: Optimizing Cleft & Craniofacial Team Care during COVID-19 using an on-line social paediatrics screening instrument. (21st October 2022) - Fisher, Emily; Szostek, Lisa; Ponton, Ethan; Lau, William; Loock, Christine
Abstract: Background: Public health mandates associated with COVID-19 added unprecedented stress on families, providers and the health care systems; including our ambulatory multidisciplinary cleft team care. In order to continue to provide responsive, multidisciplinary team (MDT) cleft and craniofacial care, it was essential to identify direct and indirect impacts of COVID-19 on our patients and families, whilst planning ahead for ongoing coordinated surgical, pediatric, and psychosocial interventions. Our team developed a short on-line psychosocial screening questionnaire that was administered prior to our MDT clinics, using a "What Matters to You" quality improvement (QI) format. Objectives: 1.To establish and test the utility of a "What Matters to You" quality improvement (QI) questionnaire. 2.To use this questionnaire in order to understand the impact of the COVID-19 pandemic on patients and family access to health services. Design/Methods: Our team developed a 5-question online smartphone-accessible survey and distributed this to families prior to their MDT clinic visit during the COVID-19 pandemic. We analyzed survey results from May 2020-October 2021 in order to understand the impact of COVID-19 on families as well as the utility of our survey system. Results: Out of 110 sequential MDT visits, families reported that COVID impacted timely access to health services (20%); employment (32%); basic needs like food and shelter (13%); and social capital. Almost half (47%) reported less than 5 people to turn to for extra support. The most common concerns caregivers have about their children were development, learning, and/or school progress (38%); mental health (36%) and social emotional well-being (31%). Conclusion: Our study shows that 5 key psychosocial screening questions can be utilized to facilitate care coordination, responsiveness, and triage for in-person and virtual care settings, and respond to family centred care priorities in the midst of evolving COVID-19 landscapes.